The effects of rice husk on the compaction properties of peat soil - Nur Fatihah, Muhamad (2013)
Soil stabilization has been extensively used for the improvement of peat soils, in enhancing the shear strength and limiting the deformation behaviour. Cement is widely used as a stabilizing materials for soils, but the increasing price is causing economic concerns among practitioners and clients alike. The quest for alternative cheaper stabilizing agents is therefore more urgent than before. Rice husk is a major agricultural waste in Malaysia and the common disposal method of open burning has notoriously contributed to environmental pollution. The possibility of admixing rice husks with cement for stabilizing soft soils could be a solution to both problems. This study was aimed to investigate the effect of rice husk on the compaction properties of peat soil. Laboratory experiment were carried out on a stabilized peat soil to determine the optimum water content, maximum dry density of the soil and waste for various mixes of rice husk. Peat soil samples were collected from Kampung Tanah Putih, Pekan, Pahang. The stabilized specimens were prepared with the peat soil admixed with various quantities of rice husk and water content, then compacted using Standard Proctor Test. The specimens were observed to undergo reduction in compressibility and increase in strength highlighting the great potential of rice husk as an alternative soil stabilizer.